2005
DOI: 10.1007/s00109-005-0677-x
|View full text |Cite
|
Sign up to set email alerts
|

TLR-2 gene Arg753Gln polymorphism is strongly associated with acute rheumatic fever in children

Abstract: The recently described family of toll-like receptors (TLRs) is a key player in host immunity by mediating inflammatory reactions against a wide range of pathogens. Mutations and polymorphisms in TLRs have revealed the importance of TLRs in human defence against diseases. TLR-2 is reported to interact with different bacterial structures, including lipoproteins, peptidoglycan and lipoteichoic acid. To assess the role of TLR-2 gene polymorphism in acute rheumatic fever (ARF) etiopathology, 61 independent Caucasia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
71
1
5

Year Published

2006
2006
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 118 publications
(81 citation statements)
references
References 39 publications
4
71
1
5
Order By: Relevance
“…These data are supported by previous reports of populations from Germany (39,47,59), Turkey (6,14), Iran (1), and the Netherlands (58). A clear difference, however, was present in the Vlax-Roma, gypsies living in Bosnia-Herzegovina, Romania, Albania, and Hungary (30), in which a small number of individuals were heterozygous for this polymorphism.…”
Section: Discussionsupporting
confidence: 92%
“…These data are supported by previous reports of populations from Germany (39,47,59), Turkey (6,14), Iran (1), and the Netherlands (58). A clear difference, however, was present in the Vlax-Roma, gypsies living in Bosnia-Herzegovina, Romania, Albania, and Hungary (30), in which a small number of individuals were heterozygous for this polymorphism.…”
Section: Discussionsupporting
confidence: 92%
“…Recent studies suggested that TLR may regulate and contribute to the pathogenesis of diseases with non-infectious tissue injury, since elevated expression of TLRs has been described in such diseases or pathological states [10,53], and TLR polymorphisms have been associated with the susceptibility to certain diseases [54][55][56][57]. For example, inactivation of the MyD88 pathway led to a reduction in atherosclerosis through a decrease in macrophage recruitment to the artery wall that was associated with reduced chemokine levels [58].…”
Section: Tlrs and Lung Injurymentioning
confidence: 99%
“…Immunology of mitral valve stenosis are strongly associated with the pathogenesis of acute RF and may indeed intensify the inflammatory reactions taking place. 22,23 Furthermore, researchers are in the early stages of understanding several other genes associated with enhanced RHD progression. These include polymorphisms of ficolin-2, a pattern-recognition protein important to the lectin complement pathway; 24 C-509T and T869C polymorphisms of transforming growth factor β-1, a cytokine secreted by most immune cells that controls their differentiation, proliferation, and state of function; 25,26 and polymorphism of interleukin 1 (IL-1) receptor antagonist, a cytokine that normally modulates IL-1-related inflammatory processes.…”
Section: Genetic Predispositionmentioning
confidence: 99%